Self-adaptive coordination for fuel-constrained robot teams with periodic and aperiodic communications. (September 2022) - Kenzin, Maksim; Bychkov, Igor; Maksimkin, Nikolai
This paper introduces a novel mission-planning scheme to coordinate a heterogeneous team of mobile robots under fuel and communication constraints. The proposed scheme has a two-level structure, where the upper level is responsible for scheduling team communication, recharging and regrouping activities, while the lower level provides plans and routes for individual group members. Such decomposition allows us to relieve an overall group routing problem by singling out the harshest constraints as a separate time-management problem. Thus, the high-level planning problem is to construct a group schedule ensuring both the efficient refuelling order and the required communication periodicity. The problem is formulated in terms of workforce scheduling problems and a hybrid evolutionary algorithm is developed to solve it. The lower-level module is to arrange emergent team communication sessions in case of unpredicted events. This original problem combines features of vehicle routing problems and special aspects of multi-agent network spreading models. A few simple ruled-based heuristics are presented to treat the problem in a timely manner.